Nail Assessment in Psoriasis and Psoriatic Arthritis (NAPPA): development and validation of a tool for assessment of nail psoriasis outcomes. (1st March 2014) - Augustin, M.; Blome, C.; Costanzo, A.; Dauden, E.; Ferrandiz, C.; Girolomoni, G.; Gniadecki, R.; Iversen, L.; Menter, A.; Michaelis‐Wittern, K.; Morita, A.; Nakagawa, H.; et al.
Summary: Background: Existing tools for nail psoriasis are complex and may not adequately measure outcomes that are important to patients. Objectives: We have developed and validated a new tool, the Nail Assessment in Psoriasis and Psoriatic Arthritis (NAPPA), with three components: a questionnaire assessing quality of life (NAPPA‐QoL), a two‐part questionnaire assessing patient‐relevant treatment benefits (the Patient Benefit Index, NAPPA‐PBI) and a psoriasis Clinical Assessment of Severity (NAPPA‐CLIN). Methods: Development of the questionnaires involved multiple steps: (i) collection of items about nail psoriasis‐related impairments and treatment goals; (ii) selection of 48 items by an expert panel, including patients; (iii) translation into eight languages; (iv) feasibility testing and (v) longitudinal validation in six countries. Results: Patients found the questionnaires clear (84%) and comprehensible (95%). NAPPA‐QoL and NAPPA‐PBI scores correlated moderately with clinical outcomes [e.g. Nail Psoriasis Severity Index (NAPSI)] and markedly with other quality‐of‐life questionnaires (e.g. EQ‐5D™). Both questionnaires were sensitive to change. Internal consistency was good (Cronbach α ≥ 0·88 for all scales). The NAPPA‐CLIN, a brief version of NAPSI that involves assessment of only four digits rather than all 20, was found to correlate highly with total NAPSI score ( r = 0·97, P < 0·001). Conclusions: Overall, the three‐component NAPPA tool is a valid, reliable and practical instrument to assess patient‐relevant nail psoriasis outcomes.